1999
DOI: 10.1289/ehp.99107141
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and morphological condition of wild mink (Mustela vison) and river otters (Lutra canadensis) in relation to chlorinated hydrocarbon contamination.

Abstract: We assssed dloinated hydrbon ontamation of mink and river otter on the Columbia and Fraser River systems ofnorthwestern North America, in relation to morphological measures ofcondition. We obtained camusses of mink and river otters from commercial tpers during the winters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
10
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 13 publications
(6 reference statements)
4
10
1
Order By: Relevance
“…Four samples collected from the lower Columbia River from 1990 to 1992 had a geometric mean concentration of 755 ng/g, whereas three samples from the upper portion of the river in Canada had a mean concentration of 165 ng/g (calculated from data reported by Elliot et al [33]). Harding et al [4] reported a total PCB concentration of 700 ng/g in a pooled sample collected from the lower Columbia River in Canada from 1994 to 1996. Concentrations in two pooled samples from the upper portion of the river ranged from 100 to 130 ng/g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four samples collected from the lower Columbia River from 1990 to 1992 had a geometric mean concentration of 755 ng/g, whereas three samples from the upper portion of the river in Canada had a mean concentration of 165 ng/g (calculated from data reported by Elliot et al [33]). Harding et al [4] reported a total PCB concentration of 700 ng/g in a pooled sample collected from the lower Columbia River in Canada from 1994 to 1996. Concentrations in two pooled samples from the upper portion of the river ranged from 100 to 130 ng/g.…”
Section: Discussionmentioning
confidence: 99%
“…Henny et al [3] reported an inverse correlation between baculum and testes size and PCBs and other OC compounds in juvenile river otters in Oregon, whereas Harding et al [4] reported an inverse correlation between PCBs and baculum length in juvenile mink, but not in river otters, collected in British Columbia. Grove [5] analyzed a much larger number of male river otters collected in Oregon and Washington.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct studies of reproduction in wild mink have seldom been attempted and have not met with success. However, recent field studies in western North America have revealed negative correlations between liver PCB concentrations in wild mink and otters and baculum (penis bone) length and testes size (Harding et al, 1999) at considerably lower PCB concentrations than those measured in Great Lakes mink.…”
Section: Introductionmentioning
confidence: 86%
“…These endocrine disruptors may cause a variety of problems with growth, development, reproduction, and behavior (Kavlock et al 1996). Gonadal abnormality and reproductive impairment caused by endocrine disruptors have been documented in fish (Edmunds et al 2000;Gimeno et al 1997;Gray and Metcalfe 1997), turtles (Guillette et al 1994(Guillette et al , 1996Willingham and Crews 1999), minks (Harding et al 1999;Heaton et al 1995), and birds (Fry et al 1987;Halldin et al 1999). However, information about gonadal differentiation in amphibians involving endocrine disruptors is relatively scarce.…”
mentioning
confidence: 99%